Topographic Hotspots of Southern Ocean Eddy Upwelling - Yung, Claire K.; Morrison, Adele K.; Hogg, Andrew McC. (Frontiers in Marine Science, 2022)
The upwelling of cold water from the depths of the Southern Ocean to its surface closes the global overturning circulation and facilitates uptake of anthropogenic heat and carbon. Upwelling is often conceptualised in a zonally averaged framework as the result of isopycnal flattening via baroclinic eddies. However, upwelling is zonally non-uniform and occurs in discrete hotspots near topographic features. The mechanisms that facilitate topographically confined eddy upwelling remain poorly understood and thus limit the accuracy of parameterisations in coarse-resolution climate models. Using a high-resolution global ocean sea-ice model, we calculate spatial distributions of upwelling transport and energy conversions associated with barotropic and baroclinic instability, derived from a thickness-weighted energetics framework. We find that five major topographic hotspots of upwelling, covering less than 30% of the circumpolar longitude range, account for up to 76% of the southward eddy upwelling transport. The conversion of energy into eddies via baroclinic instability is highly spatially correlated with upwelling transport, unlike the barotropic energy conversion, which is also an order of magnitude smaller than the baroclinic conversion. This result suggests that eddy parameterisations that quantify baroclinic energy conversions could be used to improve the simulation of upwelling hotspots in climate models. We also find that eddy kinetic energy maxima are found on average 110 km downstream of upwelling hotspots in accordance with sparse observations. Our findings demonstrate the importance of localised mechanisms to Southern Ocean dynamics.